(untitled) (Research, Society and Development, 2022)
Introduction: The health sector has incorporated and improved tools that facilitated the execution of procedures and the management of information, which has enabled greater security, agility and resolution in the provision of services. Objective: To describe the factors that hinder the use of technologies in the management of work processes and in health care. Method: Integrative literature review carried out through databases indexed in the Virtual Health Library (VHL), using the descriptors: “Safety Management”, “Health Management” and “Technology”. Eleven studies were selected. Results: Technology is a great ally in the health context, improving processes, reducing working time and financial expense to repair possible failures. Despite this, the limitation of financial resources is a limiting and frequent factor in many hospitals, corroborating the lack of investments for the acquisition or maintenance of technologies for the management of work processes and health care practices. Final Considerations: A participatory management with sufficient skills is necessary to identify and analyze the real needs of the services and the resources available to be used in the different demands of daily health care.